2022
DOI: 10.1039/d2ee00288d
|View full text |Cite
|
Sign up to set email alerts
|

Optimized carrier extraction at interfaces for 23.6% efficient tin–lead perovskite solar cells

Abstract: This work provides an efficient way to facilitate both electron and hole extraction in the designated interfaces of perovskite solar cells. A record power conversion efficiency of 23.6% for mixed Sn–Pb perovskite solar cell devices is realized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
334
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(348 citation statements)
references
References 96 publications
14
334
0
Order By: Relevance
“…The optimal certified power conversion efficiency (PCE) for a lead (Pb) halide perovskite solar cell (PSC) has now reached over 25% [ 1 ]. Similarly, the highest reported PCE of a mixed tin–lead (Sn–Pb) PSC is 23.6%, realized after treatment with ethylenediammonium (EDA) and glycinium (GlyH) as surface passivators [ 2 ]. Despite this notable success, current Sn–Pb alloyed PSCs still display stubborn shortcomings in terms of stability.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal certified power conversion efficiency (PCE) for a lead (Pb) halide perovskite solar cell (PSC) has now reached over 25% [ 1 ]. Similarly, the highest reported PCE of a mixed tin–lead (Sn–Pb) PSC is 23.6%, realized after treatment with ethylenediammonium (EDA) and glycinium (GlyH) as surface passivators [ 2 ]. Despite this notable success, current Sn–Pb alloyed PSCs still display stubborn shortcomings in terms of stability.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we found that an ideal bandgap perovskite (1.3-1.4 eV) with a 33% limit efficiency is a more ideal candidate as it can lead to a better energy level matching with an NIR polymer, which greatly differs the perovskites used in from previous IPBSCs having a broader bandgap. [30][31][32][33][34] The well-matched energy levels yield efficient charge transfer for both electrons and holes. Benefitting from ideal-bandgap perovskite, well-matched energy levels, extensive NIR solar absorption and effective passivation effects enabled by a strong interaction between the perovskite and the BHJ layer, the integrated solar cells showed simultaneously improved V OC , J SC , and FF, yielding unprecedented PCEs in both inverted PSCs and IPBSCs.…”
Section: Introductionmentioning
confidence: 99%
“…After the success of Pb-based PSCs, the Sn-based PSCs have also achieved rapid progress in promoting efficiency. Sn-Pb mixed perovskites Cs 0.1 FA 0.6 MA 0.3 Pb 0.5 Sn 0.5 I 3 based solar cells have achieved efficiency over 23.6%, [27] and pure Sn-based FASnI 3 perovskite have reached the efficiency of 14.8%. [28] In addition to the bandgap red-shift toward the optimal region, the intrusion of the Sn anion at the B site has a substantial impact on the structural stability of the 3D perovskite.…”
Section: Introduction 1why Ma Br-free and Sn-based Perovskitesmentioning
confidence: 99%